Role of acute-phase proteins in postpartum endometritis diagnostics (literature review) - T V Batrakova; T V Vavilova; N A Osipova (IP Berlin A.V., 2016)
The modern data and actual specificity of postpartum endometritis diagnostics are shown in this literature review, dynamics of C-reactive protein at physiological puerperas and septic complications.